2016
DOI: 10.1136/bmjopen-2015-009268
|View full text |Cite
|
Sign up to set email alerts
|

Associations of vitamin D status, bone health and anthropometry, with gross motor development and performance of school-aged Indian children who were born at term with low birth weight

Abstract: ObjectivesThere is little information regarding motor development of children born at term with low birth weight (LBW), a group that constitutes a large proportion of children in South Asia. We used data from infancy and at school age from a LBW cohort to investigate children's motor performance using causal inference.DesignCross-sectional follow-up study.SettingDelhi, India.ParticipantsWe recruited 912 children aged 5 years who had participated in a trial of vitamin D for term LBW infants in the first 6 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 41 publications
4
19
0
2
Order By: Relevance
“…The findings from this study are in accordance with findings from the same cohort when neurodevelopment was measured in early childhood [13]. The findings are also similar to those from a cohort study in India, where vitamin D status in early childhood was not associated with the gross motor functioning among school aged children [36]. Studies that have examined the association between cord blood vitamin D concentrations and neurodevelopment measured in early and middle childhood have shown mixed results [37,38].…”
Section: Discussionsupporting
confidence: 90%
“…The findings from this study are in accordance with findings from the same cohort when neurodevelopment was measured in early childhood [13]. The findings are also similar to those from a cohort study in India, where vitamin D status in early childhood was not associated with the gross motor functioning among school aged children [36]. Studies that have examined the association between cord blood vitamin D concentrations and neurodevelopment measured in early and middle childhood have shown mixed results [37,38].…”
Section: Discussionsupporting
confidence: 90%
“…This correlation was confirmed with previous studies that reported that the deficiency in vitamin D may be related to poor PA,30 adiposity, minimal sun exposure,31–33 and insufficient dietary intake or impairments in metabolic activation of the vitamin 3437. In addition, vitamin 25(OH) D deficiency was significantly reported in healthy growing children and adolescents in many countries,46116 and it was significantly correlated with higher levels of serum sBAP, which may contribute to both optimizing bone mass and muscle strength 117…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D plays a role in calcium and phosphorus metabolism, thus contributing to bone growth and reorganisation. In addition, vitamin D plays a role in reducing oxidative stress, antimicrobial defence, immunoregulation, anti‐inflammation, anticancer properties, neuroprotective factors and child development …”
mentioning
confidence: 99%